Moderating Effect of Green Image: The Influence of Beta on Stock Return - Sailendra, Sailendra (PT. Riset Press International, 2023)
This study aims to analyze the influence of green image on beta and stock return by considering the moderating effect of green image. The research sample consists of 44 proper companies listed in the Indonesia Stock Exchange (IDX) from 2018 to 2022, with a total of 220 year-observations. The study was analyzed using SEM-PLS statistics. The results indicated that green image does not have a significant impact on stock returns but shows a positive directional relationship. Similarly, beta also has no significant effect on stock returns but shows a positive relationship. As a moderating variable, green image moderates the effect of beta on stock returns in a negative direction. This study concludes that companies with a weak green image tend to experience a decrease in stock returns, and vice versa. In this case, green image acts as a moderating factor that affects the strength of the relationship between beta and stock returns. The findings of this study have important implications for practitioners and decision makers in evaluating and improving corporate image related to environmental issues. In addition, this study contributes to the academic literature in the accounting, finance and sustainability by providing a better understanding of the relationship between green image, beta, stock returns, and relevant moderating factors.